Collaborations Between Institutions and Industry in Naval Deck Engineering (Enhancing Sustainability in Maritime Education) - Larsen Barasa; Ahmad Wahid; Natanael Suranta; Melinasari Nurhasanah Hutagaol; Marudut Bernadtua Simanjuntak (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to examine how sustainability practices are integrated into naval deck engineering curricula and how industry-academia collaborations influence students' readiness for the maritime sector's green transition. Although sustainability is increasingly mandated by international maritime regulations — including the IMO's EEXI, CII, and the EU Emissions Trading System — no prior qualitative study has systematically assessed the integration gap from the simultaneous perspectives of industry experts, lecturers, and graduates within Indonesian naval deck engineering programs, representing the specific research gap this study addresses. A qualitative case study design was employed, with data collected through semi-structured interviews and focus group discussions with 30 participants: 5 maritime industry experts, 12 naval deck engineering lecturers, and 13 recent graduates from Indonesian maritime polytechnic institutions. Data were analyzed through a six-phase thematic analysis procedure with intercoder verification (Cohen's Kappa κ = 0.83) and validated through source triangulation and member checking. Three overarching themes emerged: curriculum integration gaps, technology content deficits, and insufficient industry collaboration depth. The study's principal scientific contribution is the demonstration that the sustainability education gap in Indonesian naval deck engineering is driven by a structural curriculum governance problem — the absence of formal industry co-design mechanisms — rather than by instructor knowledge deficits or student motivation issues, a finding that reorients the reform agenda from content addition to governance restructuring. Findings provide actionable recommendations for maritime polytechnics, the Ministry of Transportation, and IMO maritime education stakeholders.